Research advances in the application of recognition elements in the detection of mycotoxins in grains - HAN Yi-tao; LI Ke-jing; LUO Fei; LI Rui; LI Chun-hua; XIE Gang (Liang you shipin ke-ji, 2020)
Mycotoxin contamination is one of the key elements arousing grain safety problems and challenges, which are thus the increasingly focus- and hot-spot research area at global level. Hence, the development of fast-time, high-accuracy, low-cost, and simple-operation detection methods for monitoring mycotoxin is critical to the guarantee of grains afety and quality. During the whole process of biosensor, specificity and selectivity of recognition elements is prerequisite for the excellent analytical performance. This paper summarized the forms of major recognition elements reported in previous publications in the last few years, and reviewed the application of biosensors based on recognition elements in monitoring mycotoxins, and the main problems existing in this researching stage were also proposed, which could provide novel ideas and new sights into the development of related studies.